Determining The Quantities Knives of The Chopper of Cotton Stems (Texas Journal of Multidisciplinary Studies, 2022)
The article gives the importance of grinding cotton stalks before chilly plowing, which helps to increase soil plowing and urazhinost. For this purpose, a cotton stem shredder was developed and the results of a theoretical study of the working process of a cotton shredder are given.